Effect of tellurium promoter on vanadium phosphate catalyst for partial oxidation of n-butane - Yap, Taufiq Yun Hin; Sairi, Nor Asrina; Hutchings, Graham John; Dummer, Nicholas F.; Bartley, Jonathan K. (Elsevier, 2011)
Te-promoted (1%) vanadium phosphate catalyst (VPDTe) was prepared via VOPO4·2H2O by calcining its precursor VOHPO4·0.5H2O in a flow of n-butane/air. VPDTe catalyst has resulted a higher existence of V5+ phase with V5+/V4+ ratio of 0.23. SEM micrographs show that Te addition altered the arrangement of the platelets from “rose-like” clusters to layer with irregular shape. Te addition has also markedly lowered the reduction activation energies of the vanadium phosphate catalyst as revealed by TPR profile. The amount of active oxygen species associated with V4+ phase of the Te promoted catalyst was significantly higher than those of the unpromoted catalyst. These observations suggest that high mobility and availability of reactive oxygen species contributed to the enhancement of n-butane conversion up to 80% at 673 K, while only 47% over unpromoted catalyst (2400 h−1, 1.7%n-butane in air).